Functional-semantic interpretation of the desire modality in Ibero-Romance languages - N. Zenenko (Ибероамериканские тетради, 2018)
The article contains the analysis of the ways of expression of desire modality using functional-semantic approach. This approach, being productive in modern linguistic methodology is able to provide research strategy of semantic and functional properties of language units. Problems of desire modality are of great interest to modern linguistics. The author examines topical issues of functionalsemantic grammar, with an emphasis on functional-semantic category of desire.